2020
DOI: 10.1093/ibd/izaa240
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of CD3+CD8- and CD3+CD8+ T Cells to TNF-α Overexpression in Crohn Disease–Associated Perianal Fistulas and Induction of Epithelial-Mesenchymal Transition in HT-29 Cells

Abstract: Background Fistulas represent a frequent and severe complication in patients with Crohn disease (CD). Tumor necrosis factor-alpha (TNF-α), transforming growth factor-beta, and interleukin (IL)-13 are known to trigger epithelial-mesenchymal transition (EMT), promoting fistula formation. Here, we investigated the role of T-lymphocytes (T cells) in fistula pathogenesis. Methods CD3+CD8-, CD3+CD8+, or CD45+CD3- cells from healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 30 publications
(26 reference statements)
0
18
0
Order By: Relevance
“…Although the notion of the involvement of CD8 + T cells in IBD has been long considered and published ( 12 , 17 ), new attention has been given in more recent years (for summary of articles see Table 1 ). Throughout the years, the role of CD8 + T cells in IBD has been controversial, with some reports indicating anti-colitogenic properties ( 11 , 42 44 ) with others showing their contribution to tissue inflammation ( 5 , 12 , 16 18 , 20 , 31 , 36 , 39 , 45 47 ). Such ambivalent findings might be explained, at least partially, by the source from where CD8 + T cells were obtained (e.g.…”
Section: Cd8 + T Cells Contribute To the Pathogenesis Of Ibdmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the notion of the involvement of CD8 + T cells in IBD has been long considered and published ( 12 , 17 ), new attention has been given in more recent years (for summary of articles see Table 1 ). Throughout the years, the role of CD8 + T cells in IBD has been controversial, with some reports indicating anti-colitogenic properties ( 11 , 42 44 ) with others showing their contribution to tissue inflammation ( 5 , 12 , 16 18 , 20 , 31 , 36 , 39 , 45 47 ). Such ambivalent findings might be explained, at least partially, by the source from where CD8 + T cells were obtained (e.g.…”
Section: Cd8 + T Cells Contribute To the Pathogenesis Of Ibdmentioning
confidence: 99%
“…Moreover, Boschetti and colleagues found that circulating and mucosal GrB + perforin + Tc1 cells are abundant in Crohn’s disease patients with endoscopic recurrence, compared to endoscopic remission and controls ( 39 ). In addition, Bruckner et al reported on the inflammatory effects of Tc1 cells on the mucosa of Crohn’s disease patients leading to fistulas ( 31 ), common ulcers in up to 50% of the patients. In fact, activated perforin + Tc1 cells are increased in the affected intestinal mucosa of active stages of the disease course in IBD patients ( 12 , 17 ).…”
Section: Ibd Could Be In Part Initiated and Further Developed By Activated Cytotoxic Cd8 + T Cells (Tc1)mentioning
confidence: 99%
“…Both T-cell subsets secreted high amounts of TNF- and interleukin (IL)-13 in co-culture experiments, both of which are recognized as key cytokines in the pathogenesis of fistulating CD ( Figure 1 ). 14 …”
Section: Histopathogenesismentioning
confidence: 99%
“…Particularly, around the fistula tract, CD4 + cells were highly present. Then, both cell subsets promoted the expression of EMT-related genes when co-cultured with HT-29 cells [ 42 ].…”
Section: Emt Process In Fistula Formationmentioning
confidence: 99%